Sistem Informasi Pendistribusian Hasil Ternak Dan Pengolahan Data Pakan Ternak Berbasis Web - Farida Yusuf; Asrul Azhari Muin; Anggriani Anggriani (Jurusan Sistem Informasi Universitas Islam Negeri Alauddin Makassar, 2021)
The development of technology is speedy and accurate, making us live side by side with information and technology itself. Many people have abandoned searching for information manually and switched to using computerized systems so that they can access information more quickly. The animal market is one of the regional assets in improving the community's economy. This animal market also distributes cattle. This distribution requires a fast, precise and accurate time. Animal markets also carry out the processing of animal feed which is used as its animal feed and for sale. In processing data on animal feed ingredients, there are also obstacles; for example, from the production side, errors often occur in recording data for feed ingredients and the amount of feed production and its processed products. This study aims to design and build an information system to distribute livestock products and data processing for animal feed in the animal market.